Abu Syed Abd al-Hay bin Dahhak, the author of Zeen al-Akhbar - Masomi, Mohammad Bashir; Yoldash, Nooradin (Integrated Journal for Research in Arts and Humanities, 2024)
Abdul Hai Gardizi is the author of Zain al-Akhbar or Tarikh Gardizi, one of the most famous historians of Afghanistan. He is considered among the last historians of the first Ghaznavid period and his work, Zain al-Akhbar, is one of the important sources of the country's history. In this article, we have tried to briefly introduce Gardizi and the book Zain al-Akhbar and to evaluate Gardizi's historiographical method in writing Zain al-Akhbar as much as possible. The useful information it provides about the events of the first Ghaznavid period are very important and valuable in the history of Afghanistan. Gardizi has also dealt with social and ethnological topics and issues and has presented valuable and useful reports in this field, which distinguishes him from other historians. Gardizi was less religiously prejudiced than his contemporary historians and to some extent provided valuable information about the religions and rituals of Hindus, Jews, Christians and followers of other religions.